Tracing soil erosion with Fe3O4 magnetic powder: Principle and application - Hongqiang Shi; Gang Liu; Xiaobing An; Yajun Zhao; Fenli Zheng; Hairu Li; Xunchang (John) Zhang; Xuncheng Pan; Binglong Wu; Xuesong Wang (International Soil and Water Conservation Research, 2024)
Magnetic powder is regarded as an effective and economical tracer for estimating soil erosion. However, the principle and application for using magnetic powder to estimate soil erosion are still not fully developed. In this study, magnetic powders with mean diameters of both 30 and 1 μm were mixed into three soils at different mass proportion. The relationship between magnetic susceptibility and the mass proportion of the introduced magnetic powder in the tagged soil, and the binding ability of magnetic powder to soil particles after both dry and wet sieving were investigated. The accuracy of tracking soil loss by using magnetic powder as a tracer was assessed. The results showed that there was a significant linear relationship between the magnetic susceptibility and the mass proportion of the introduced magnetic powder in the tagged soil. The relationship between the amount of soil captured by a magnet and the mass proportion of magnetic powder in the tagged soil indicated that soils were readily magnetized by magnetic powder, especially fine fractions. The magnetic susceptibility of magnetic powder in different sizes of soil aggregates was variable. A majority of magnetic powder of both 30 and 1 μm diameters was strongly bound with fine particles <0.05 mm in dry and wet sieving. Using the estimated tracer mass proportions, the relative errors between measured and estimated soil losses with enrichment correction factor were less than 18.3% under the simulated rain events. This study not only reveal the principle of Fe3O4 powder in soil erosion, but also improve its estimated precision of soil loss, which can make the tracing method by Fe3O4 magnetic powder more useable in future.